A web-application that extends functionality of medical device for tumor treatment by means of electrochemotherapy - Pavlović, Ivan (Radiology and oncology (Ljubljana), 2004)
Electrochemotherapy (ECT) is a novel method for efficient tumor treatment in clinical environment. It combines local drug delivery and application of shorthigh voltage pulses, which permeabilize the plasma membrane by electroporation. Drug can enter only the cells with permeabilzed membrane. Recently, medical device CliniporatorTM for controlled electroporation was developed. Here, we present a web-application that extends the functionality of this medical device. The aim of the application is to collect, store and toallow the analysis of every ECT application using this medical device. The application helps transferring data collected by devčce during the electroporation process to the central database, and enables filling of medical records through the web forms. The application is based on technologies ASP, HTML, Flash, JavaScript, XML and others. The application main advantages are easy and rapid data access, scalability and independence of client computer operating system as well as easy application debugging and upgrading.
Keywords: drug; kemoterapija; medicinski aparati; rak (medicina); spletne strani; therapy; zdravila; zdravljenje